PENINGKATAN KEAHLIAN MENYIMAK SISWA DENGAN UJI MENYIMAK MELALUI TOEFL DI SMA DEK PADANG - Edwar Kemal (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2020)
As a medium of instruction, English does not easily develop in Indonesia. It is even becoming a problem in communication where many parties are not interested to use it in communication. On the contrary, world of Industries really demand the workers to be able to speak and write in English well. SMA DEK as one of the private school that its graduated students directly work in companies after graduation answers the problem. It provides its students with various English program such as english day, English zone, learning TOEFL and English Proficiency. By considering the quality of the students, these programs are expected running well. Emphasizing listening skill is the main purpose because it is the most activity used by students during English learning. So that, observation method, testing method and discussion method are implemented in order to find out the student qualification to answer the challenge. From the community service implementation, it is found that the students have been good on listening skill understanding. During the participant observation, they make and answer the question freely. While implementing the listening TOEFL test, they can answer the questions well and when the discussion method comes, they argue about the correct answer by giving their own reason. It finally concludes that, by learning the Listening TOEFL test, SMA DEK students are motivated to speak freely and give comment toward the given information.